2009
DOI: 10.1111/j.1939-1676.2008.0257.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Deafness in Dogs Heterozygous or Homozygous for the Merle Allele

Abstract: Background: Deafness in dogs is frequently associated with the pigment genes piebald and merle. Little is known about the prevalence of deafness in dogs carrying the merle allele.Objective: To determine the prevalence of deafness in dogs heterozygous and homozygous for the merle allele of the mouse Silver pigment locus homolog (SILV) gene.Animals: One hundred and fifty-three privately owned merle dogs of different breeds and both sexes. Methods: Hearing was tested by brainstem auditory-evoked response and clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…Histological studies have shown that inner ear structures develop physiologically prior to and after birth with atrophy of the stria vascularis occurring between the first and the fourth week of age in affected dogs (Johnsson et al, 1973;Strain et al, 2009). The age of the dogs included in our study ranged from 4 to 184 weeks, at which age the organ of Corti was fully developed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histological studies have shown that inner ear structures develop physiologically prior to and after birth with atrophy of the stria vascularis occurring between the first and the fourth week of age in affected dogs (Johnsson et al, 1973;Strain et al, 2009). The age of the dogs included in our study ranged from 4 to 184 weeks, at which age the organ of Corti was fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…CCSD results from degeneration of the stria vascularis and the hair cells as well as from the collapse of Reissner's membrane and the saccule in the inner ear. It can be pigment associated or neuroepithelial (Strain, 2015). The recessive alleles of the piebald locus (S) and the dominant alleles of the merle locus (M) are suspected of instigating hereditary deafness, although the causative genes and mode of inheritance have not been determined (Strain, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that this report found more bilateral deafness than unilateral, when other published reports, studying other breeds, found a higher prevalence of unilateral than bilateral, is certainly the result of the small sample size. Deafness in dogs is frequently associated with altered expression of pigment genes, such as piebald and merle (Strain et al 2009), and several prior studies have identified statistically significant associations between deafness and a blue iris colour and white coat pigmentation (Strain 2004, Platt et al 2006, Famula et al 2007). Since not all dogs with piebald are deaf or have blue eyes, it can be argued that this variable outcome is the consequence of incomplete penetrance of a causative gene, or that one or more additional genes regulate the expression of the pigment gene (Strain 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…The coat color pattern is seen in the Collie, Australian Shepherd, Shetland Sheepdog, Catahoula Leopard Dog, Cardigan Welsh Corgi, Dachshund, and Great Dane breeds, and less commonly in the Chihuahua, American Pit Bull Terrier, American Staffordshire Terrier, Beauceron, Border Collie, Coolie, and others [3,4].…”
Section: Introductionmentioning
confidence: 99%